Fracture resistance of metal-ceramic crown copings cemented to two types of intra-radicular posts - Priscila Alonso HENRIQUES; André Hayato SAGUCHI; Fábio Valverde Rodrigues BASTOS NETO; Igor PROKOPOWITSCH; Angela Toshie ARAKI
Abstract Introduction Endodontically treated teeth are more susceptible to root fracture than vital teeth. In order to reduce the risk of fracture, the use of intra-radicular posts and crowns is indicated. However, their own fracture resistance remains unclear. Objective To analyze the behavior of metal-ceramic crown copings cemented to two types of intra-radicular posts under tensile stress. Material and method Sixteen metal-ceramic crown copings cemented with zinc phosphate cement to cast metal posts and cores (group 1, n = 8) or with self-adhesive resin cement to glass-fiber posts rebased with composite resin (group 2, n = 8) were subjected to tensile testing after endodontic treatment and standardized preparation. Failure occurred when the crown coping and/or post-core assembly fractured and/or detached. Result In group 1, after the application of a mean tensile load of 46.83 N, 7 crown copings and metal cores separated as a whole, while in 1 specimen the coping detached from the metal core. In group 2, a mean tensile load of 127.68 N resulted in glass-fiber post fracture, and in 1 case the entire crown-post-core assembly was detached. Tensile strength differed significantly between the two groups (p = 0.0085). Conclusion Our findings suggest that metal-ceramic crown copings cemented with self-adhesive resin cement show strong adhesion to composite resin cores associated with glass-fiber posts, thus providing a safe alternative to the use of cast metal posts and cores.